Pengaruh Pendidikan, Pembentukan Modal Tetap Bruto, Internet dan Upah Minimum Provinsi Terhadap Penyerapan Tenaga Kerja Formal di Pulau Sumatera - Muhammad Feryansyah; Hilmiatus Sahla (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the effect of education, gross fixed capital formation (PMTB), internet, and provincial minimum wage (UMP) on formal labor absorption in Sumatra. The analytical method used is panel data regression with a Fixed Effect Model (FEM) approach and a sample size of 50 observations consisting of 10 provinces in Sumatra during the observation period 2020-2024. The results show that partially, the education variable has no effect on formal labor absorption in Sumatra. Meanwhile, the variables of gross fixed capital formation, internet, and provincial minimum wage partially influence formal labor absorption in Sumatra. In addition, simultaneously, the variables of education, gross fixed capital formation, internet, and provincial minimum wage influence formal labor absorption in Sumatera.